La production culturelle comme continuation du militantisme par d’autres moyens ? - Abir Kréfa (Revue des Mondes Musulmans et de la Méditerranée)
Since the beginning of the 1980’s in Tunisia, literature and edition have represented an alternative sphere for some former radical leftists and leftist opponents. Based on interviews with Tunisian editors and writers conducted for a sociology dissertation, this article highlights these biographical evolutions. It grants importance to how the actors perceive their literary and publishing activities, as well as to the dispositional and contextual conditions that have made these biographical changes possible. These changes can be explained by the dispositions and skills acquired during the activist experience, but they also have much to do with the characteristics of the literary sphere, the audience of wich remains – until nowadays – relatively scarce. Although the activist careers of these editors and writers have been diverse and sometimes divergent, their literary and publishing activities reduce the opposition between engagement and disengagement. Therefore, edition and literature have represented a way of « continuing political commitment » by other means and at a lower cost.